PENERAPAN SISTEM INFORMASI GEOGRAFI DALAM PENDUGAAN SEBARAN DAERAH RAWAN LONGSOR DI KECAMATAN NGARGOYOSO, KABUPATEN KARANGANYAR - Reza Muhammadi; Mochtar Luthfi Rayes; Istika Nita (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2019)
Ngargoyoso Sub-district is one of the areas that have the potential of landslides. To find out and observe landslide hazard, it is necessary to identify and mapping the area. This study was conducted from November 2017 to April 2018 at nine villages in Ngargoyoso sub-district. The method of the study was scoring of rainfall, slope, land use, geology, permeability, texture and effective depth of soil. The landslide-prone area were classified into three classes, i.e., low, medium, and high of landslide-prone. Low landslide-prone class had characteristics of flat slope with land uses are in the form of settlement, plantation, rice field and moor. The dominant areas are located in the land mapping units of 1,3,4,5 and 9 in Dukuh, Nglegok and Puntukrejo Villages. Medium landslide-prone class had characteristics of steep to very steep slope with land uses are in the form of forest/plantation, settlement, shrubs and rice field. The dominant areas are the in the land mapping units of 3, 4, 5, 6, 7, 8, 10, 11, 12, 14 and 15, that dominant in Girimulyo, Kemuning, Jatirejo and Nglegok Villages. High landslide-prone class had characteristics of steep slopes to very steep slopes with land uses of forest/plantation land use, shrubs, and rice fields. High landslide-prone class was dominant in Berjo, Ngargoyoso and Segorogunung Villages that are in te land mapping units of 6,7, 8, 11, 12, 13, 15 and 16. The validation result of landslide-prone area map showed the accuracy level of 85.71%.